2016
DOI: 10.1080/19381980.2016.1248325
|View full text |Cite
|
Sign up to set email alerts
|

The risks and benefits of sun exposure 2016

Abstract: Public health authorities in the United States are recommending that men, women and children reduce their exposure to sunlight, based on concerns that this exposure will promote skin cancer. On the other hand, data show that increasing numbers of Americans suffer from vitamin D deficiencies and serious health problems caused by insufficient sun exposure. The body of science concerning the benefits of moderate sun exposure is growing rapidly, and is causing a different perception of sun/UV as it relates to huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
102
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 123 publications
1
102
0
6
Order By: Relevance
“…Previous studies have shown that more than 40% of people got sunburnt during their holiday. It is worth mentioning that sunburns are associated with a doubling of the risk of melanoma because of the development of mutations in melanocytes (9). Ultraviolet rays cause mutations in skin cells and an accumulation of cancer-causing mutations leads to more cases of cancer in older compared to younger people.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that more than 40% of people got sunburnt during their holiday. It is worth mentioning that sunburns are associated with a doubling of the risk of melanoma because of the development of mutations in melanocytes (9). Ultraviolet rays cause mutations in skin cells and an accumulation of cancer-causing mutations leads to more cases of cancer in older compared to younger people.…”
Section: Discussionmentioning
confidence: 99%
“…The potential shortcomings of this study, including lack of statistical significance [4,12], difference in use pattern [12,13] between the US (mainly for intentional, intermittent sun exposure) and Australia (mainly for regular, non-intentional sun exposure), as well as inconsistencies in site [14] between sunscreen application (only to the face and upper extremities) and melanoma-occurring sites (over the whole body), have been discussed. It was reported that for the efficacy evaluation of sunscreens, the gold standard of double-blind, randomly controlled clinical studies cannot be carried out because of ethical concerns [4].…”
Section: Introductionmentioning
confidence: 98%
“…Apparently based on a sun avoidance policy, broad-spectrum sunscreens have been recommended in the United States (US) as an adjunct to help prevent sunburns, skin cancers and premature aging (i.e., photoaging) for persons older than 6 months, even on cloudy days [1]. In view of reports that daily exposure to mild or moderate sunlight may not have noticeable long-term adverse effects on skin aging [2], skin aging may be mainly caused by the intrinsic nutritional factor [2], and such an exposure may also provide numerous potentially important health benefits [3][4][5][6][7], Chiou [8] recently suggested that in our daily lives we may not need to use sunscreen and other sun protection methods, such as seeking shade, wearing long-sleeved shirts, long pants and broad-brimmed hats unless one is to be exposed to potentially sunburn-causing sunlight. In this regard it is of interest to note that subtropical Australia and New Zealand, with the highest melanoma incidence rates in the world, are probably the only two countries to date to adopt the World Health Organization (WHO) guidelines on a sun protection program that recommend use of sunscreens only when the solar UV Index is ≥ 3 [8 -10].…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing numbers of Americans suffer from vitamin D deficiencies and serious health problems caused by insufficient sun exposure necessary for endogenous vitamin D synthesis. In addition, sunscreens reduce vitamin D production, prompting recommendations to warn about vitamin D deficiency associated with their use . For these reasons alone, vitamin D is considered an important nutrient for inclusion in dietary supplements aimed at photoprotection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sunscreens reduce vitamin D production, prompting recommendations to warn about vitamin D deficiency associated with their use. 49 For these reasons alone, vitamin D is considered an important nutrient for inclusion in dietary supplements aimed at photoprotection. However, vitamin D also exhibits anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%